2016
DOI: 10.3389/fmicb.2016.00240
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biostimulation Using Sewage Sludge, Soybean Meal, and Wheat Straw on Oil Degradation and Bacterial Community Composition in a Contaminated Desert Soil

Abstract: Waste materials have a strong potential in the bioremediation of oil-contaminated sites, because of their richness in nutrients and their economical feasibility. We used sewage sludge, soybean meal, and wheat straw to biostimulate oil degradation in a heavily contaminated desert soil. While oil degradation was assessed by following the produced CO2 and by using gas chromatography–mass spectrometry (GC–MS), shifts in bacterial community composition were monitored using illumina MiSeq. The addition of sewage slu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 91 publications
1
18
0
Order By: Relevance
“…While previous studies have applied HTS to characterize crude oil contaminated soils (Al-Kindi and Abed 2016), this study is the first to characterize the microbial community in tropical ULO-contaminated soil using combined fingerprinting and Illumina MiSeq techniques. The increased sequencing depth associated with HTS allows for the identification of rare bacteria and provided access to the genetic diversity of microbial assemblages in these ULO-contaminated soils.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have applied HTS to characterize crude oil contaminated soils (Al-Kindi and Abed 2016), this study is the first to characterize the microbial community in tropical ULO-contaminated soil using combined fingerprinting and Illumina MiSeq techniques. The increased sequencing depth associated with HTS allows for the identification of rare bacteria and provided access to the genetic diversity of microbial assemblages in these ULO-contaminated soils.…”
Section: Discussionmentioning
confidence: 99%
“…Culture-independent approaches using both, 16S rRNA genes (Jiao et al, 2016 ) and functional genes (Yang et al, 2014 ), have been used for isolation of diverse bacteria from petroleum contaminated soils. There are more studies focusing on the succession of bacterial community structures in oil-contaminated soils during bioremediation (Ai-Kindi and Abed, 2016 ; Leewis et al, 2016 ; Pacwa-Plociniczak et al, 2016 ; Wu et al, 2016 , 2017 ). It has been shown that bacterial compositions differ significantly between culture-dependent and -independent methods (Stefani et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…There have been many reports that the biodegradation of organic pollutants by indigenous microorganisms is promoted only by the supplementation of nutrients ( Chang et al, 2010 ; Karamalidis et al, 2010 ; Ai-Kindi and Abed, 2016 ) and that treatment with nutrients can be more efficient than the supplement of exogeneous microorganisms because exogeneous microorganisms will sometimes fail to survive and grow in contaminated sites ( Atlas, 1995 ; Margesin and Schinner, 2001 ; Bento et al, 2005 ; Thompson et al, 2005 ). However, the degradation test showed that the inoculation of a microbial consortium clearly improved the TPH decrease in the contaminated soil.…”
Section: Resultsmentioning
confidence: 99%
“…To accomplish successful bioremediation, many issues, including the types of organic compound present, the use of appropriate biodegrading microorganisms and their biodegradation properties, and diverse environmental factors such as water content, temperature, pH, and heavy metal content should be addressed ( Gandolfi et al, 2010 ; Jeon and Madsen, 2013 ), but are not easily resolved due to their complexity. However, these limitations may be easily overcome by the application of a microbial consortium consisting of multiple strains with diverse biodegradation abilities and physiological properties that ensure survival in a contaminated site with diverse environmental conditions ( Rahman et al, 2002 ; Thompson et al, 2005 ; Wu et al, 2012 ; M′rassi et al, 2015 ; Ai-Kindi and Abed, 2016 ; Li et al, 2016 ; Gurav et al, 2017 ). In this study a native microbial consortium, complying with international law and national legislation for biological resources, was constructed using microbial strains that were isolated from Korea, for the bioremediation of diesel fuel-contaminated soil in Korea.…”
Section: Introductionmentioning
confidence: 99%